Developing a smart scheduling application for the android - Loh, Wei Xian. (2010)
Scheduling work, appointments and other tasks on hand is an important aspect of city dwellers‟ daily lives. Besides work, time is also set aside for entertainment such as meeting friends for dinner or going out for movies etc. Moreover, with the current trend on Social Networking, people are organizing events and inviting people out using technology such as the Facebook website.